Response of Alexandria Cockerels Reproductive Status to GnRH (Receptal) Injection - Elnagar, Samar A. (International Journal of Poultry Science, 2009)
Fourty, 40 weeks old Alexandrian cockerels were distributed among 4 treatments to study the effect of GnRH analogue (Receptal) administration, on their reproductive performance. Birds of the second, third and fourth group were individually intramuscularly injected weekly with 0.1, 0.2 and 0.4 ml of Receptal, respectively for 2 months. Birds of the first group served as control. Receptal had significantly increased testosterone. Birds injected with the 0.1 and 0.2 ml of Receptal had significantly higher ejaculated volume as it increased by 49 and 38% respectively. On the other hand, the highest dose of Receptal decreased the ejaculate volume to 52 and 56% of the untreated males’ volume on the first and second month, respectively. Birds injected with the 0.1 and 0.2 ml of Receptal had significantly higher sperm concentration as it increased by 28 and 18% respectively, meanwhile, raising the Receptal dose to 0.4 ml did not show any significant difference. The 0.1 and 0.2 ml doses of Receptal had significantly higher motility as it increased to reach 133 and 129% of control respectively, meanwhile, birds treated with 0.4 ml of Receptal had similar sperm motility as the controls. Cholesterol has increased significantly in a dose dependent manner. Total protein did not show significant differences except with the medium dose of Receptal as it increased to reach 112% of controls level. Seminal plasma constitutes showed a reflection of the blood status. It was concluded that the synthetic GnRH was capable of improving 40 week old cockerels’ reproductive status.